Desain Mesin Penetas Telur Berbasis Internet of Thing (IoT) Menggunakan Android - Jati Isnawang, Jalu Sancoko; Widodo, Wahyu; Muhima, Rani Rotul (Institut Teknologi Adhi Tama Surabaya, 2024)
Chicken farmers already have tools to hatch chicken eggs, but the tool still works manually. Manually, in the sense that the eggs still need to be turned over so that the heat produced by the egg-hatching incubator is evenly distributed throughout the egg, the selection of eggs to be hatched still uses light bulbs to see the conditions inside the egg. One way to overcome this is to increase the role of the incubator into an egg incubator that works according to the commands embedded in the Arduino nano microcontroller and add an interface via an Android smartphone that will facilitate monitoring. This research has produced an Android-based Monitoring application created using the Java programming language and a prototype of an automatic egg incubator using Arduino Nano as a microcontroller, Esp32-Cam to send sensor data to the server, DHT22 as a temperature and humidity sensor, and Relay as a regulator of the components on or off. The controller regulates all activities in the automatic egg incubator to hatch eggs into chicken seeds, and the egg-hatching process becomes easier, more efficient and practical. The egg incubator that has been designed has a very low hatching success rate of 11.1% from the calculation of the success rate formula and the success rate table from the calculation; this machine has not succeeded in hatching on a large scale, while for network testing with Quality Of Service (QOS) using the Wireshark Application, the average results were 25Kbit/s Throughput, 5.91 m/s Delay (Very good), 5.03 m/s Jitter (Good), and 0% packet loss (Very good) according to the category table.